2004
DOI: 10.1175/1525-7541(2004)005<0922:dwccit>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Water Content Changes in the Bare Soil of a Coastal Desert

Abstract: The deposition of dew is a common meteorological phenomenon that has been recognized as an important ecosystem element, especially in arid areas. There is some evidence that indicates that there is an increase in the water content of the topsoil during nights in which no dew deposition was observed. The purpose of this study is to describe the daily pattern of changes in water content in the upper soil layers and to identify the mechanism by which water is added to the soil (deposition or direct absorption). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 36 publications
(19 reference statements)
3
17
0
Order By: Relevance
“…Other important factors that could explain why we found that the total average water gain in bare soil (1.42 mm day -1 ) was twice the daily average WVA found by Verhoef et al (2006) are: (i) the clay content in that study was somewhat lower than in ours (14.8% compared with 17.7%), (ii) our study plot is closer to the coast than the Coria area (17 km from the southern coast of the city of Alicante compared to 80 km), and there are no mountains between the coast and the ''El VentĂł s'' area. The total average water gain we found is within the range of WVA detected by Kosmas et al (2001) (from 0.05 to 3.7 mm day -1 ) but higher than the mean WVA measured by Agam and Berliner (2004) in the Negev desert in Israel (0.25 mm day -1 ). Like Domingo et al (1999) in a Retama sphaerocarpa stand in AlmerĂ­a (Spain), we found good correspondence of transpiration from S. tenacissima calculated from the Clumped Model and transpiration measured by the porometer method (Fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Other important factors that could explain why we found that the total average water gain in bare soil (1.42 mm day -1 ) was twice the daily average WVA found by Verhoef et al (2006) are: (i) the clay content in that study was somewhat lower than in ours (14.8% compared with 17.7%), (ii) our study plot is closer to the coast than the Coria area (17 km from the southern coast of the city of Alicante compared to 80 km), and there are no mountains between the coast and the ''El VentĂł s'' area. The total average water gain we found is within the range of WVA detected by Kosmas et al (2001) (from 0.05 to 3.7 mm day -1 ) but higher than the mean WVA measured by Agam and Berliner (2004) in the Negev desert in Israel (0.25 mm day -1 ). Like Domingo et al (1999) in a Retama sphaerocarpa stand in AlmerĂ­a (Spain), we found good correspondence of transpiration from S. tenacissima calculated from the Clumped Model and transpiration measured by the porometer method (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…In these environments, where rainfall is scarce and light, if any, there may be other important dry-season ''non-rainfall'' soil water input from fog and dew formation (Kidron 2000(Kidron , 2005Malek et al 1999;Seely 1976;Shanyengana et al 2002;Zangvil 1996) or soil water vapour adsorption (WVA) (Agam and Berliner 2004;Kosmas et al 1998Kosmas et al , 2001. These processes can supply vegetation with water vital for survival in seasons with a severe water deficit, giving rise to a close relationship between soil water dynamics and plant water response.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore chose a value of 2%, still very dry but elevated slightly above minimum to reflect these adjacent sources of water. The value of 2% is in the low end of observations of soil moisture in desert soils reported in the literature (Scanlon, 1994;Agam (Ninari) and Berliner, 2004).…”
Section: Calculation Of the Pm 10 Emission Ratementioning
confidence: 73%
“…2), direct water vapor adsorption and soil internal evaporation are also thought to contribute to total daytime evaporation in the cool dry season. Furthermore, previous studies of arid and semiarid regions showed that actual dew deposition on a bare soil surface is probably rare because the dew-point temperature is lower than the soil surface temperature due to the lack of water vapor content (WVC) in the atmosphere (Agam and Berliner, 2004). In contrast, this study showed that the dew-point temperature is higher than or equal to the soil surface temperature.…”
Section: Resultsmentioning
confidence: 99%